Synthesis of Renewable Diesel from Pure Plant Oil of Kapuk (Ceiba pentandra) Seed Using NiMo/-Al2O3 Catalysts - Permana, Edwin; Wasistha, Excel Emerlan Samiar; Heriyanti, Septina Is; Murti, Sri Djangkung Sumbogo; Marlinda, Lenny; Tarigan, Indra Lasmana (Jurnal Rekayasa Kimia & Lingkungan, 2022)
Ceiba pentandra (Kapok) is a tropical plant belonging to the Malvales that contain palm oil. Naturally, Pure Plant Oil (PPO) can be used as a renewable energy source that is a promising energy alternative instead of fossil. Somehow, one of the effects of the quality of Pure Plant Oil (PPO) is the presence of unsaturated bonds and the presence of oxygen. The most appropriate method to overcome these problems is hydrodeoxygenation using a batch system autoclave reactor. In the present work, we synthesized of Green Diesel using hydrodeoxygenation and NiMo/-Al2O3 catalyst to saturate double bonds and remove oxygen. The yield of pure plant oil was 42.77-74.72% while the yield of green diesel at pressure conditions of 30 and 50 bar and at temperatures of 300, 350 and 400C produced 76.73 94.06%. Then, the best condition for the hydrodeoxygenation reaction for the biggest yield is at a pressure of 50 bar at 350C. The results of the characterization of gas products using GC-TCD showed the composition of gases H2, O2, CO, CH4, and CO2. Whereas for green diesel liquid products, pure plant oil, and kapok seed oil were analyzed using GC-MS obtained hydrocarbon compounds with interval C10-C20. Quality analysis of kapok seed oil, pure plant oil, and green diesel has been in accordance with quality standards except for FFA and viscosity.